Improving Prospective Primary School Teachers’ Skill in Playing Gamelan Degung: An Action Research in Indonesia (Harmonia: Journal of Arts Research and Education, 2018)
Prospective primary school teachers had low skill in playing gamelan degung (Indonesian Gamelan). To improve skills in playing gamelan degung correctly, prospective primary school teachers need to be taught techniques of ringing, muffling (menengkep), and memorizing the compositions. Therefore, this research seeks to improve students in playing gamelan degung. The action research report presented in this article exemplified the work of the involved collaborative team in making reflective-critical steps to change the students’ ability from their initial state of being unable to play gamelan degung properly to be able to play gamelan composition properly. The results of the action had shown changes in the ability of students in playing gamelan degung with 97.6% skill change level of the students and 57.15% success rate of students improving from the inept category to the adept category in playing gamelan degung. As a result, the skills of prospective primary school teachers in playing gamelan degung can be improved through some development steps in action research.